MYSTISM IN THE SULUK AND JAWOKAN OF THE CIREBON-DERMAYU COMMUNITY IN LITERARY INTERTEXTUALITY THROUGH WRITING LEARNING IN HIGH SCHOOL - Taiman (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research aims to explore, analyze and understand the use of suluk and jawokan in the context of the culture and traditions of the Cirebon-Indramayu community. The type of research used is a qualitative descriptive study with an ethnographic approach to document the use of suluk and jawokan in various traditional ceremonies, rituals, as well as aspects of the social and spiritual life of the community. Data collection methods include direct observation, in-depth interviews, and searching related literature. The research results show that suluk and jawokan have an important role in traditional ceremonies, traditional medicine, and religious rituals, used for various purposes such as healing, protection, and communication with ancestral spirits. Apart from that, suluk and jawokan reflect cultural values ​​and local wisdom passed down from generation to generation. This research concludes that preserving suluk and jawokan as part of intangible cultural heritage is very important to maintain the identity and cultural sustainability of the people of Cirebon-Indramayu. The mysticism of suluk and jawokan is oral literature that developed among the people of Cirebon-Indramayu as a vehicle for expression in expressing ethics, aesthetics and transcendent values ​​in deeper social and religious realms. Based on the research results, the students' writing level is very enthusiastic, so that students are able to express ideas, thoughts, and messages in writing poetry or mantras. It turns out that based on the table, 70% of students like writing, 15% dislike it, and 15% are hesitant. Learning to write requires continuous practice. For this reason, teachers as facilitators and motivators for students, should offer strategies in the form of methods and media that are interesting for students. The strategies used by teachers determine the success of learning. To achieve writing skills, a lot of practice is needed. Appropriate and varied writing exercises will make it easier for students to learn the language and have a big influence on learning other subjects. Therefore, the role of teachers and their creativity in the learning process also determines the success of students in learning the language, especially writing lessons.